The Correlation of Intention, Social Support, Information Accessibility, and Personal Autonomy on Indonesian Health Insurance (JKN) Membership - Sugondo, Sugondo; Rohendi, Acep; Halim, Abdul (Lambung Mangkurat, 2024)
The Indonesian National Social Security Council (DJSN) reported that Banjarbaru City is in the top 4 regencies which JKN membership rate is below 90%. The results of data analysis also represent that non-Contribution Support Recipients (PBI) members with low membership levels are non-wage earners (PBPU). Guntung Manggis Health Center working area contributes to the low membership rate. This study aims to analyze the determinant factors related to independent JKN membership in related to intention, social support, accessibility of information, and personal autonomy. The population in this study are people who have lived in the Guntung Payung Community Health Center working area for at least the last 6 months, with the number of samples is 96 respondents. The findings of logistic regression in this analysis indicate that there is an influence between intention (p = 0.05; EXP(B) = 3.770), social support (p = 0.001; EXP(B) = 8.816), and information accessibility (p = 0.0001; EXP(B) = 12.554) with JKN Mandiri membership. This research suggests that National Health Service (BPJS) be able to maximize promotion programs, disseminate information to the community, and be able to collaborate with other sectors to increase community membership rate in the JKN Mandiri program.